The Research on Soft Pneumatic Actuators in Italy: Design Solutions and Applications - Maria Paterna; Carlo De Benedictis; Carlo Ferraresi (Actuators, 2022)
Interest in soft actuators has increased enormously in the last 10 years. Thanks to their compliance and flexibility, they are suitable to be employed to actuate devices that must safely interact with humans or delicate objects or to actuate bio-inspired robots able to move in hostile environments. This paper reviews the research on soft pneumatic actuators conducted in Italy, focusing on mechanical design, analytical modeling, and possible application. A classification based on the geometry is proposed, since a wide set of architectures and manufacturing solutions are available. This aspect is confirmed by the extent of scenarios in which researchers take advantage of such systems’ improved flexibility and functionality. Several applications regarding bio-robotics, bioengineering, wearable devices, and more are presented and discussed.